ANGI-16. NOTCH SIGNALING IN BEVACIZUMAB-INDUCED VASCULAR NORMALIZATION IN GLIOBLASTOMA. Issue 11 (6th November 2017) - Saito, Norihiko; Aoki, Kazuya; Hirai, Nozomi; Fujita, Satoshi; Iwama, Junya; Nakayama, Haruo; Hayashi, Morito; Ito, Keisuke; Sakurai, Takatoshi; Iwabuchi, Satoshi
Abstract: Tumor angiogenesis occurs in the setting of a defective vasculature, which is associated with increased vascular permeability and enhanced tumor permeability. Bevacizumab is used to treat malignant glioma and was found to reduce microvascular density and prune abnormal tumor microvessels. Using electron microscopic observation of two autopsy cases, we investigated the effects of blood vessel normalization in glioblastomas treated with bevacizumab. Notch-1 and SMA immunostaining were used to compare initial surgical specimens with postmortem specimens obtained after bevacizumab treatment. Postmortem samples showed marked proliferation of SMA-positive cells (pericytes) in tumor vessels and marked proliferation of Notch-1–positive cells around vessels. Electron microscopic images confirmed the presence of pericytes surrounding the vascular endothelium. These findings suggest that bevacizumab treatment promotes vascular normalization by recruiting mature pericytes. Next, we investigated the effects of bevacizumab on VEGF inhibition in glioma stem cells. Bevacizumab treatment attenuated activation of VEGFR2 and increased Notch signaling expression. VEGF inhibition by bevacizumab treatment attenuated proliferation and self-renewal of glioma stem cells and induced endothelial and pericyte differentiation. In tumor angiogenesis, vascular endothelial growth factor induces sprouting angiogenesis and recruitment of vascular endothelial cells such as tip cells, stalk cells, and phalanx cells. Fully mature phalanx cells are in close contact with pericytes. Our results suggest that bevacizumab treatment induces glioma stem cells to differentiate to endothelium and pericytes. These mechanisms might be important in normalizing tumor vasculature after bevacizumab treatment and could be useful in improving the effectiveness of current glioma therapy.